Using IEC materials for mass communication: experiences of an Arsenic mitigation project in Bangladesh - Hossain, Zabed; Quaiyum, Md.; Jakariya, Md. (BRAC Research and Evaluation Division (RED), 2019)
Different types of lEC materials were used in BRAe's arsenic mitigation project (June 1999-December 2001). Printed lEC (Information. education. and communication) materials included posters. leaflets. stickers. booklets. carry folders. flashcards. class routine cards. prayer time clocks. and letters. The effectiveness of these materials is assessed. Experiences gained in using them to communicate With rural people are discussed. The findings are expected to help policy makers in selecting appropriate printed lEC materials to raise awareness among the arsenic affected people of Bangladesh.